2013
DOI: 10.1111/iej.12092
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury due to anaphylactic shock as a result of formocresol used during root canal treatment

Abstract: A type-I allergic reaction can be induced by formocresol. The reasons for the brain injury are thought to be cerebral hypoxia, which was induced by the anaphylactic shock and/or cerebral parenchymal oedema. All dentists should be aware of the risks involved in the use of formocresol and avoid using materials containing formocresol and related agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…There are issues regarding possible sensitivity to some of the medicaments used (Ding et al . ), and staining or possible discoloration of the tooth has been reported (Nosrat et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are issues regarding possible sensitivity to some of the medicaments used (Ding et al . ), and staining or possible discoloration of the tooth has been reported (Nosrat et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…It increases the number of visits, the need for temporization, patient compliance, attendance issues, increasing the treatment time and cost of treatment (Nosrat et al 2012). There are issues regarding possible sensitivity to some of the medicaments used (Ding et al 2013), and staining or possible discoloration of the tooth has been reported (Nosrat et al 2012). It has also been shown that these intracanal medicaments may impact adversely on dentine fracture resistance (Yassen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was suggested that anaphylactic shock causes brain injury by inducing cerebral hypoxia due to hypoperfusion following hypotension [14]. The hypoxia response system, which is mediated by the transcriptional activator HIF-1α, functions as a key regulator of oxygen homeostasis that facilitates both oxygen delivery and adaptation to oxygen deprivation [15].…”
Section: Resultsmentioning
confidence: 99%
“…Anaphylaxis is a serious allergic reaction that is rapid in onset and may cause death associated with systemic vasodilation [1,3] resulting in hypotension and hypoxic brain damage [14]. The rhythmic patterns of Buk music use duple-division (2) and mixed-division (2 + 3 or 3 + 2) beats, and just as poems sound musical and resonant, the sound of a Buk has its own musical flowing rhythms and sequences.…”
Section: Discussionmentioning
confidence: 99%
“…, Ding et al . ) and the use of AH Plus (Stutz et al . ), and hypersensitivity to zinc oxide (Karabucak & Stoopler ).…”
Section: Introductionmentioning
confidence: 99%